Kompensasi, Kinerja, Kepuasan Dan Pengaruhnya Terhadap Loyalitas Karyawan Dengan Pendekatan Path Analys Studi Pada BPRS HIK - Berlianingsih Kusumawati; Sulistyo Seti Utami (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2016)
This study aims to: (1) to analyze the influence of compensation on employee loyalty, (2) to analyze the effect of the performance of the employee against employee loyalty, (3) to analyze the effect of job satisfaction on employee loyalty, and (3) to analyze the effect of compensation, employee performance and satisfaction working simultaneously on employee loyalty. The research method used descriptive-quantitative approach path analysis. Path analysis is atechnique for analyzing the causal relationships that occur in multiple regression if the independent variables affect the dependent variable not only directly, but also indirectly. The results of this study concluded that: first, compensation Directly Affects the loyalty. Second, the performance Directly Affects the loyalty. Third, satisfaction Directly Affects the loyalty. Fourth, Compensation indirect effect on loyalty through the performance and through. Fifth, Performance indirect effect on loyalty through compensation amounting and through the satisfaction. And sixth, Satisfaction indirect effect on loyalty through compensation of and through the performance.